Free vibration of the system of two viscoelastic beams coupled by viscoelastic interlayer - Cabanska-Placzkiewicz, K. (Інститут гідромеханіки НАН України, 1999)
An analytical method of solution of the free vibration problem for composite system of two viscoelastic beams coupled by a viscoelastic interlayer has been proposed. The phenomenon of free vibration has been described using a homogenous system of conjugate partial differential equations. After the separation of variables in the differential equations the boundary problem has been solved and two complex sequences have been obtained: the sequence of frequencies and the sequence of modes of free vibration. The property of orthogonality of complex modes of free vibration has been demonstrated. Polyharmonic free vibration has been expanded into the complex Fourier series with respect to complex eigenfunctions. The coeffcients at the eigenfunctions are determined by the initial conditions. Запропоновано аналітичний метод розв'язку задачі про вільні коливання системи, складеної з двох в'язко-пружних балок, сполучених за допомогою в'язко-пружного проміжного шару. Вільні коливання описувались з використанням однорідної системи спряжених диференційних рівнянь у частинних похідних. Після розділення змінних у диференційних рівняннях було розв'язано граничну задачу і отримано дві комплексні послідовності: послідовність частот та послідовність мод вільних коливань. Продемонстровано властивість ортогональності комплексних мод вільних коливань. Полігармонічні вільні коливання розкладались у комплексні ряди Фур'є відносно компплексних власних функцій, коефіцієнти при яких визначаються початковими умовами. Предложен аналитический метод решения задачи о свободных колебаниях системы, состоящей из двух вязко-упругих балок, связанных при помощи вязко-упругого промежуточного слоя. Свободные колебания были описаны с использованием однородной системы сопряженных дифференциальных уравнений в частных производных. После разделения переменных в дифференциальных уравнениях была решена граничная задача и получены две комплексные последовательности: последовательность частот и последовательность мод свободных колебаний. Продемонстрировано свойство ортогональности комплексных мод свободных колебаний. Полигармонические свободные колебания раскладывались в комплексные ряды Фурье относительно комплексных собственных функций, коэффициенты при которых определяются начальными условиями.